CELIAC DISEASE IN CHILDREN. A HISTORY CASE WITH ONSET AT THE AGE OF 17 YEARS - M. O. Revnova (Вопросы современной педиатрии, 2013)
Being one of the most common representatives of malabsorbtion syndrome celiac disease has been diagnosed more and more often in Russia. Celiac disease is a hereditary condition with high prevalence and different symptoms called «Great Mimic». The article deals with diagnostics based on testing the antibodies to tTG, DPG, biopsies of the duodenum and gluten free diet. There is given an example of severe case of celiac disease in a 17-years-old boy with weight loss, delayed sexual development and severe gastrointestinal symptoms. Gluten free diet and proper treatment led to permanent remission.